Current requirements for studies of drugs for the pathogenetic treatment of multiple sclerosis - A. N. Boyko; N. N. Spirin; Ya. V. Vlasov; M. N. Zakharova (Неврология, нейропсихиатрия, психосоматика, 2019)
More than 10 multiple sclerosis-modifying drugs (MSMDs) are widely used now. Novel MSMDs should be investigated in strict accordance with the evidence-based medicine principles governing clinical trials (of both original drugs and their analogues) that prove the high efficiency, safety, and tolerability of new drugs versus the already existing ones. Russia has gained extensive experience in conducting such studies using the well-known drugs as a comparison group. The efficiency and safety of new therapy should be evaluated according to the international criteria on the basis of a sufficient number of patients during a long-term follow-up. When combining the drugs, their efficiency and the risk of adverse effects can vary. The published results of a small study of the combined drug Leucovir (Belarus) do not meet these requirements, and the possibility of using this drug to treat multiple sclerosis can be discussed only after adequate phases II and III clinical trials.